From Flower Farming to Agritourism: The Conditions of (Dis)entanglements and Material (im)mobility in Bahong, La Trinidad amid COVID-19 - Aquino, Chelsea Denise; Calanog, Jericco; Cawed, Jeydah Mari; Guce, Ma. Angelika; Guazon, Hector (anthropozine: The Official Publication of the University of the Philippines H. Otley Beyer Museum of Anthropology; Vol 1 No 2 (2023): The Flow of Things and Bodies: The Production of Flowers in La Trinidad, Benguet, 2025)
Tracing the inflows and outflows of flowers in Bahong, La Trinidad, Benguet during the COVID-19 pandemic uncovers how the owners of flower farms rely on overlapping and extending networks that have provided livelihood and shaped aspirations in times of crises.